Evaluation of pilot community art-based workshops designed for Ukrainian refugee children - Lukito, Steve; Wenkert, Michaela; Hryhorovych, Inna; Opanasenko, Svitlana; Timms, Laura; Yule, William; Ougrin, Dennis (Frontiers in Child and Adolescent Psychiatry, 2023)
Objectives: Approximately 8 million Ukrainians have been displaced by the war in Ukraine and five million children had their education disrupted. Here, we report an evaluation of (1) the feasibility (i.e., recruitment), (2) the acceptability (i.e., attendance, participants' views) and (3) the influence of a pilot community art-based project on the well-being, health behaviour and socialisation of Ukrainian refugee children in London, UK. Methods: Twentytwo refugee children aged 4-14 years from St Mary's Ukrainian school in London took part in five weekly art workshop group sessions led by a team of volunteer independent artists based in a community art studio in West London in collaboration with Children and War UK. Analyses were conducted on measures of the children's psychological well-being, health behaviour, and socialisation; collected from participating children and their parents through the workshops. Results: The community art workshops received sufficient interest from parents during recruitment. Child participants and their parents expressed overwhelmingly positive views and high satisfaction towards the workshops and their activities. While the workshops were conducted without a control group, changes in psychological well-being and health behaviour and socialisation were in the expected direction. The workshops were associated with reduced impact of intrusive re-experiencing of traumatic events (p = .021), negative emotion (ps = .006-.043; rated by children and by their parents, respectively), and sleep disturbance (p=.015). Mood and motivational states increase relative to before activities within sessions (ps = .001-.023). Conclusions: The artist-led workshops are a valuable community project associated with high satisfaction and potentially increased wellbeing in Ukrainian refugee children. A provision for a larger number of participants should be considered.